Implementation of Authentic Assessment in Islamic Cultural History Subject Within the Independent Curriculum - Sahlan, Moh; Abqoriy, Muhammad; Mawidha, Rahma Fajr (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to describe and analyze the implementation of authentic assessment in the